Regional public stock reductions in Spain: Estimations from a multiregional spatial vector autorregressive model - Miguel A. Márquez; Julián Ramajo Hernández; Geoffrey Hewings (REGION, 2017)
The estimation of the impact of public investment on regional economic growth requires consideration of the spatio-temporal dynamics among the state variables of each region. Recent austerity policies in Spain that feature temporary decreases in the accumulation of regional public capital should thus be evaluated in terms of their impact on the economy as a whole, on specific regions together with the spillovers effects from one region to the rest of the regional system. Applying a multiregional integrated specification to model interdependencies across regions, our results indicate that, while global decreases in public investment have a homogenously negative effect on the output of all the regions, the Spanish regions portray heterogeneous responses from localized public capital stock reductions over the simulation period considered.
Keywords: 330; Regional investment; Public capital stock; Spillovers; Multiregional; Spatial econometrics; Vector autoregressions